2021
DOI: 10.7759/cureus.14993
|View full text |Cite
|
Sign up to set email alerts
|

Acute Peptic Ulcer Disease Caused by Non-Helicobacter pylori-Helicobacter

Abstract: Human infection by Non-Helicobacter pylori-Helicobacter is rare and most commonly transmitted through direct contact with animals. The clinical presentation in most cases is chronic epigastric abdominal pain and it usually leads to chronic gastritis. We present an uncommon case of a patient with acute onset abdominal pain secondary to acute peptic ulcer disease caused by Helicobacter heilmannii who underwent successful treatment. We also conducted a review of the literature to understand the epidemiology, etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Helicobacter species are Gram-negative, curved bacilli commonly found in the gastrointestinal environment of humans ( 1 , 2 ) and animals ( 3 , 4 ). Recently, non- Helicobacter pylori species have been considered emerging human pathogens since they have been reported in clinical cases ( 5 7 ) that are often acquired through direct contact with infected animals ( 8 ). Therefore, there is an urgent need to understand the full nature of their pathogenesis.…”
Section: Announcementmentioning
confidence: 99%
“…Helicobacter species are Gram-negative, curved bacilli commonly found in the gastrointestinal environment of humans ( 1 , 2 ) and animals ( 3 , 4 ). Recently, non- Helicobacter pylori species have been considered emerging human pathogens since they have been reported in clinical cases ( 5 7 ) that are often acquired through direct contact with infected animals ( 8 ). Therefore, there is an urgent need to understand the full nature of their pathogenesis.…”
Section: Announcementmentioning
confidence: 99%
“…2 Although H. heilmannii are distinct from the more commonly known Helicobacter pylori (H. pylori), the bacteria have been associated with similar symptoms, including dyspepsia and abdominal pain, as well as micro-and macroscopic inflammation in humans. [3][4][5] Gastric carcinoma, and mucosa-associated lymphoid tissue (MALT) lymphoma, though rare, have also been associated with the infection. 6,7 The diagnosis of H. heilmannii requires identification of the spiral-shaped bacteria during histologic examination of gastric mucosal biopsies obtained during an endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Since Dent et al first reported on the presence of H. heilmannii in humans in 1987, 1 several subtypes ( H. suis, H. felis, H. bizzozeronii, H. salomonis, H. cynogastricus , and H. baculiformis ) have been identified using 16S RNA analysis 2 . Although H. heilmannii are distinct from the more commonly known Helicobacter pylori ( H. pylori ), the bacteria have been associated with similar symptoms, including dyspepsia and abdominal pain, as well as micro‐ and macroscopic inflammation in humans 3–5 . Gastric carcinoma, and mucosa‐associated lymphoid tissue (MALT) lymphoma, though rare, have also been associated with the infection 6,7 …”
Section: Introductionmentioning
confidence: 99%